Association between cyberbullying and suicidal behaviour among adolescents in Peninsular Malaysia - Fadhli, Siti Aisyah Mohd (2022)
Background: Suicidal behaviour among adolescents’ incidence is on the rise and becoming a worldwide public health concern. In addition, the growth in technology and social media engagement has contributed to the rise of cyberbullying. Cyberbullying habits are becoming more pervasive and have recently triggered tragic suicides where previous studies reported significant association between cyberbullying and suicidal behaviour. There are limited studies on association between cyberbullying and suicidal behaviour among adolescents which the main key of this study. Objective: To determine the association between suicidal behaviour and cyberbullying amongst adolescents in Peninsular Malaysia. Methodology: A crosssectional school study was conducted among 1290 secondary school adolescents aged 13 to 17 years old in Peninsular Malaysia via multistage cluster sampling. Malay version of cyberbullying scale, study proforma and Malay version of Patient Health Questionnaire-9 were used to assess suicidal behaviour (dependent variables), cyberbullying (independent variable), and other confounders of suicidal behaviour (independent variables) among adolescents. Simple and multiple logistic regression were used to determine the association between cyberbullying and suicidal behaviour using SPSS version 26. Results: The response rate of this study was 89.6%. The prevalence of cyberbullying victimization among adolescents was 13.7% and cyberbullying perpetrator was 3.8%. The prevalence of suicidal behaviour among adolescents was 17.1% where 11.9% had suicidal thought, 10.2% had suicidal plan and 8.4% had suicidal attempt. Multiple logistic regression revealed that those who were cyberbullying victimization had 2.35 times odds of suicidal behaviour as compared to those who were not cyberbullying victimization (AOR:2.35,95% CI: 1.50, 3.69; p <0.001), when adjusted for other confounders. Frequency of cyberbullying victimization and cyberbullying perpetrator were not significant factors (p=0.264, p= 0.984 respectively). Other significant factors were age (95% CI: 0.69, 0.94; p=0.005), gender (95% CI: 2.11, 6.25; p <0.001), perceived social support from family members (95% CI: 1.52, 4.09; p <0.001), perceived social support from friends (95% CI: 1.21, 3.19; p=0.006), history of abuse (95% CI: 1.47, 3.54; p <0.001), parents engage in fight in front of children (95% CI: 1.38, 3.49; p=0.001) and depression status (95% CI: 5.04, 11.28; p <0.001). Conclusions: An alarming number of adolescents in Peninsular Malaysia who were involved in cyberbullying and its significant association with suicidal behaviour warrant the need to strengthen the present program to curb the issues.